Exploring hTERT promoter methylation in cutaneous T‐cell lymphomas. Issue 9 (12th October 2021) - Chebly, Alain; Ropio, Joana; Peloponese, Jean‐Marie; Poglio, Sandrine; Prochazkova‐Carlotti, Martina; Cherrier, Floriane; Ferrer, Jacky; Idrissi, Yamina; Segal‐Bendirdjian, Evelyne; Chouery, Eliane; Farra, Chantal; Pham‐Ledard, Anne; et al.
Abstract : Cutaneous T‐cell lymphomas (CTCLs) are telomerase‐positive tumors expressing hTERT, although neither gene rearrangement/amplification nor promoter hotspot mutations could explain the hTERT re‐expression. As the hTERT promoter is rich in CpG, we investigated the contribution of epigenetic mechanisms in its re‐expression. We analyzed hTERT promoter methylation status in CTCL cells compared with healthy cells. Gene‐specific methylation analyses revealed a common methylation pattern exclusively in tumor cells. This methylation pattern encompassed a hypermethylated distal region from −650 to −150 bp and a hypomethylated proximal region from −150 to +150 bp. Interestingly, the hypermethylated region matches with the recently named TERT hypermethylated oncogenic region (THOR). THOR has been associated with telomerase reactivation in many cancers, but it has so far not been reported in cutaneous lymphomas. Additionally, we assessed the effect of THOR on two histone deacetylase inhibitors (HDACi), romidepsin and vorinostat, both approved for CTCL treatment and a DNA methyltransferase inhibitor (DNMTi) 5‐azacytidine, unapproved for CTCL. Contrary to our expectations, the findings reported herein revealed that THOR methylation is relatively stable under these epigenetic drugs' pressure, whereas these drugs reduced the hTERT gene expression. Abstract : Cutaneous T‐cell lymphomas (CTCLs) represent a group of lymphoproliferative disorders arising from the skin. CTCLs are characterized by hTERT gene expression despite the lack of hTERT amplifications or rearrangements. Here, we investigated hTERT promoter methylation and associated TERT hypermethylated oncogenic region (THOR) with hTERT reactivation in CTCL. Additionally, we evaluated THOR methylation and hTERT expression after treatment with epigenetic drugs. Altogether, our study offers a better understanding of the response to epigenetic drugs in patients with CTCL.